2012
DOI: 10.1002/gcc.21959
|View full text |Cite
|
Sign up to set email alerts
|

Differential positioning and close spatial proximity of translocation‐prone genes in nonmalignant B‐cells from multiple myeloma patients

Abstract: Accumulating evidence suggests that spatial proximity of potential chromosomal translocation partners influences translocation probability. It is not known, however, whether genome organization differs in nonmalignant cells from patients as compared to their cellular counterparts from healthy donors. This could contribute to translocation potential causing cancer. Multiple myeloma is a hematopoietic cancer of the B‐lineage, characterized by karyotypic instability, including chromosomal translocations involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In a recent study, Martin et al (), showed that genome organization in MM patients differs in non‐malignant cells as compared to their cellular counterparts in healthy blood donors. This suggests that variances in genome structure may contribute to its destabilization, aberration and the modification of total transcription activities, resulting in the possibility of causing cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Martin et al (), showed that genome organization in MM patients differs in non‐malignant cells as compared to their cellular counterparts in healthy blood donors. This suggests that variances in genome structure may contribute to its destabilization, aberration and the modification of total transcription activities, resulting in the possibility of causing cancer.…”
Section: Discussionmentioning
confidence: 99%
“…To identify patients with plasma cells positive for IGH translocations, conventional FISH was used. This typical 2D fixation method has been described previously (Martin et al, ) and results in a 2D (flattened) cell adhesion to slide. Four commercial probe sets were used for each bone marrow sample: LSI IGH dual color break apart probe for the detection of chromosome breakage at the 14q32 locus; and three LSI dual color, dual fusion probes: IGH / FGFR3 for the detection of t(4;14)(p16;q32); IGH / CCND1 for the detection of t(11;14)(q13;q32), and IGH / MAF for the detection of t(14;16)(q32;q23).…”
Section: Methodsmentioning
confidence: 99%
“…Most studies of genome organization with respect to translocation potential have utilized cells from healthy donors; the assumption being that genome positioning in cells from healthy donors does not differ from positioning in non‐translocated cells from affected patients. We have previously provided evidence that IGH and FGFR3 , and not IGH and MAF , are closer together in the interphase nucleus of non‐malignant B‐cells from MM patients than in B‐cells from healthy donors, suggesting an increased translocation potential in the patient‐derived cells (Martin et al, ; Martin et al, ). We sought to investigate the idea that extra‐territorial positioning of translocation‐prone gene loci may influence translocation potential in B‐cells from healthy donors and in non‐malignant B cells from patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations